Queer asylum seekers in the European Union - Mikalsen, Hanna Randgaard (2022)
Queer asylum seekers experience discrimination and rejection at European borders. Research has established that the European Union is contradictory in how it promotes itself as a queer- friendly, but simultaneously maintains an asylum system unsuited to recognize the asylum needs of queer asylum applicants. This study aims at tackling these contradictions. Specifically, it investigates how queer asylum seekers are portrayed in the Common European Asylum System’s (CEAS) discourse. In addition, it discusses how these discourses contribute to producing homonationalism and ideas of European ideological borders. In order to answer these questions, a Critical Discourse Analysis of central CEAS policy documents has been conducted. Five thematic categories were identified in the discourse: 1) invisibility, with the subcategory 2) invisibility ? risk of overlooking, 3) stigmatization, 4) ambivalence and 5) limited representation. The analysis demonstrates several tendencies of heteronormativity and homonormativity, because the CEAS is not able to reflect the myriad of sexual orientations and gender identities that exists and their unique experiences. In addition, it indicates that the CEAS is not able to harmonize the different conceptions of sexual citizenship across the EU, resulting in an unharmonized asylum system for queer persons. The findings demonstrate tendencies of homonationalism and ideological border-making in the CEAS due to the utilization of queer identities in order to construct ideas of European citizenship vis a vis homophobic ‘others’. This is also found due to how the EU is asserting its image as a queer rights advocate, and the general saliency of queer rights in the policy documents.